Change in Quality of Life with Velopharyngeal Insufficiency Surgery. (29th June 2015) - Skirko, Jonathan R.; Weaver, Edward M.; Perkins, Jonathan A.; Kinter, Sara; Eblen, Linda; Martina, Julie; Sie, Kathleen C.Y.
Abstract : Objectives: (1) To define the minimal clinically important difference (MCID) of the Velopharyngeal Insufficiency (VPI) Effects on Life Outcomes (VELO) instrument, and (2) to test for the change in quality of life (QOL) after VPI surgery. Study Design: Prospective observational cohort. Setting: VPI clinic at a tertiary pediatric medical center. Subjects and Methods: Children with VPI and their parents completed the VELO instrument (higher score is better QOL) at enrollment and then underwent VPI surgery (Furlow palatoplasty or sphincter pharyngoplasty, n = 32), other treatments (obturator or oronasal fistula repair, n = 7), or no treatment (n = 18). They completed the VELO instrument again and an instrument of global rating of change in QOL at 1 year. The MCID was anchored to the global change instrument scores corresponding to "a little" or "somewhat" better. Within‐group (paired t test) and between‐group (Student t test) changes in VELO scores were tested for the VPI surgery and no treatment groups. The association between treatment group and change in VELO scores was tested with multivariate linear regression, adjusting for confounders. Results: Follow‐up was obtained for 37 of 57 (65%) patients. The mean (±standard deviation) change in VELO scores corresponding to the MCID anchor was 15 ± 13. The VELO score improved significantly more in the VPI surgery group (change, 22 ± 15; P <. 001) than in the no treatment group (change, 9 ± 12; P =. 04), after adjusting for confounders ( P =. 007 between groups). Conclusion: VPI surgery using the Furlow palatoplasty or sphincter pharyngoplasty improves VPI‐specific QOL, and the improvement is clinically important.